Brand store on marketing performance through customer network quality - Cristian Natalis Putra; Lauw Sun Hiong (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
A good relationship quality between business actors and consumers can encourage increased performance of MSMEs in the retail sector. This study examines the influence of brand store on marketing performance through the quality of customer networks. This study uses a quantitative approach as a research model, with a sample of 151 retail MSMEs in Pontianak selected through a purposive sampling method. Data were analyzed through Structural Equation Modeling (SEM) using the AMOS test tool version 23. This study found that brand store has a significant effect on marketing performance. The quality of customer networks can improve marketing performance, but does not show a direct impact. In addition, the quality of customer networks is unable to strengthen the relationship between brand store and marketing performance. The results show that brand store has a direct influence in improving marketing performance. Meanwhile, the quality of customer networks is not proven to play a role as a variable that strengthens the relationship between brand store and marketing performance directly.